Highly efficient unidirectional forward scattering induced by resonant interference in a metal-dielectric heterodimer - Sun, Song; Wang, Dacheng; Feng, Zheng; Tan, Wei (Nanoscale, 2020)
We demonstrate that a metal-dielectric heterodimer structure can satisfy a nearly ideal first Kerker condition at a wavelength close to the resonance peak of the dimer, yielding efficient unidirectional forward scattering with a high forward-to-backward scattering ratio ( 48 dB) and remarkable enhancement of the forward scattering intensity (∼2.68 times compared to a single dielectric nanoparticle). Using a rigorous analytical dipole-dipole interaction model, the underlying mechanism is revealed, in which the originally weak electric dipole moment of the dimer is significantly enhanced owing to the strong resonant interference between the localized surface plasmon resonance of the metal and the Mie resonances of the dielectric material, which could up-match the magnetic dipole moment of the dimer at a wavelength close to the resonance peak, boosting the forward scattering efficiency. To achieve the optimal conditions, the sizes of the metal and dielectric constituents as well as the gap distance of the dimer have to be physically and delicately tuned to ensure a perfect match in both the amplitudes and phases of the electric and magnetic dipole moments of the dimer. On top of that, the loss of the heterodimer can be effectively suppressed to a level well below that of a pure metal nanoparticle, which further benefits the forward scattering efficiency. The flexibility in designing the dimer geometry and choosing metal-dielectric material combinations enables efficient unidirectional forward scattering in a broadband spectrum (UV to visible) with an intermediate gap distance (10-20 nm), greatly expanding the application scope. The proposed hybrid dimer could serve as a powerful and versatile building block in many emergent fields such as metasurfaces, nanoantennae, etc . Interparticle resonant interference in the metal-dielectric heterodimer satisfies the first Kerker condition at its resonance peak, yielding highly-efficient unidirectional forward scattering.